(3bhGYO ef GdTGaYjI hGdMfajIs
(3ChdgG (B:s
(3GdMeO ddg ef bhGYO GdMfajI QVi Gddg Yfge Ydi QCi GdeMbbjf Cf Gdfai hGdEKHGJ EPG JYGQVG s
(3BNQgG (B:s
(3de jcf ESJOdGd CUMGHfG ai JQc GdLgQ HGdHSedI HMOjK CfS QVi Gddg Yfg HGdWQjb GdPi PcQhg HWQjb GdEjQGO Ydjge hEfeG gh HGdWQjb GdPi PcQfGg hai gPG GdbOQ caGjI def YfOg EfUGa hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3Gdabg GdESdGejs